Comparison of cardiovascular risk assessment protocols and achievement of risk factor targets in patients with type 2 diabetes - Guo, Hui; Wu, Huizhen (Frontiers in Endocrinology, 2025)
ObjectiveCompare the differences in the 10-year cardiovascular risk assessment results for patients with type 2 diabetes among various guidelines, as well as the attainment of target levels for primary cardiovascular risk factors.MethodThis study is a retrospective, real-world study that included patients with type 2 diabetes who were hospitalized at the Second Affiliated Hospital of Hebei North University from August 2023 until October 2023.This study evaluated the 10-year cardiovascular risk in patients with type 2 diabetes, as well as the attainment of target levels for blood pressure, blood glucose, and lipid levels.ResultThis study included a total of 200 hospitalized patients with type 2 diabetes, with a median age of 62.5 (57, 67), among which 97 (48.5%)were male. According to the SCORE2-Diabetes model from the European Society of Cardiology’s “2023 ESC Guidelines for the management of cardiovascular disease in patients with diabetes”, the assessment results were as follows:165 cases(82.5%) were classified as very high risk,25 cases(10%) as high risk,8 cases(4%) as medium risk, and 2 cases(1%) as low risk; According to the assessment method from the American Association of Clinical Endocrinologists’ “Comprehensive Management Algorithm for Type 2 Diabetes(2023 edition)”, the assessment results were as follows:150 cases(75%) were classified as extreme risk, 48 cases(24%) as very high risk, and 2 cases(1%) as high risk; The assessment results using the method outlined in the “Guideline for the Prevention and Treatment of Diabetes Mellitus in China(2024 Edition)”by the Chinese Diabetes Society are as follows:149 cases(74.5%) are at extremely high risk, and 51 cases(25.5%) are at high risk. There is no statistically significant difference among the assessment results of the three methods(χ²=2.759, P=0.252).Based on the criteria in the aforementioned three guidelines, the achievement rates for the main cardiovascular risk factors were assessed, with rates of 1%, 0%, and 0% respectively. There is no statistically significant difference among these results(P=0.332).ConclusionAlthough the methods for assessing 10-year cardiovascular risk and the criteria for achieving main cardiovascular risk factor targets differ among the three guidelines, there is no statistical difference in the assessment results and achievement rates among the 200 patients with type 2 diabetes.